Analysis of a Micro-CHP Unit with in-series SOFC Stacks Fed by Biogas. (August 2015) - Kupecki, Jakub; Skrzypkiewicz, Marek; Wierzbicki, Michal; Stepien, Michal
Abstract: This paper presents results of a recent evaluation of a conceptual micro-CHP units in two alternative configurations. Parallel and in-series connections of two identical commercial electrolyte-supported SOFC stacks were under evaluation. In order to achieve high overall fuel utilization in the system enabling high electrical efficiency, both concepts were analyzed with respect to operational regimes typical for SOFC stacks. Numerical analysis included several possible configurations of complete a system with fuel processor, SOFC stacks and BoP components. Evaluation of the in-series connection was performed using experimental setup with a commercial SOFC stack to reproduce operating conditions obtained from the model. Validation of the concept was necessary to qualitatively and quantitatively determine possibility of operating second stack on lean fuel originating from the anodic compartments of the first stack. Results of the comparative analysis presented in this paper were used to aid in defining optimal outline of a micro-CHP power system. Predictions of the models were in agreement with preliminary experiments, proving the concept of in-series stacks configuration viable. Electrical efficiency increases for the system with two in-series stacks, and value of 46%LHV can be achieved in the micro-CHP system with SOFC.